Evaluation of Bobwhite Quail Surveys in Kansas - Roger Wells; Keith Sexson; Gary L. Doster (National Quail Symposium Proceedings, 2017)
Statistical analysis of selected Kansas bobwhite (Colinus virginianus) population and harvest surveys is presented. Survey techniques evaluated include roadside counts by rural mail carriers (RMCS), April roadside counts, whistling cock counts, random summer brood counts (RSBC), interviews of hunters contacted during the hunting season, wing collection envelopes distributed to hunters, and a mail questionnaire harvest survey of hunters. Significant differences (P < 0.05) between years and between survey regions existed for the April RMCS, April roadside count (coveys/observer), June whistle count, RSBC (young/adult and young/adult hen), and July RMCS, Correlation tests indicated significant (P < O, 1 to 0.001) correlation coefficient (r) values between many of the population surveys, and between many of the population surveys and harvest parameters. The October RMCS is the best single predictor of harvest parameters. When the October RMCS (quail/100 miles) is used in association with adults/observer (RSBC) and total quail/observer (RSBC), higher R2 values are obtained as determined by stepwise multiple regression with harvest parameters,